Does female disadvantage mean lower access to food? - Derose, L. F.; Das Gupta, M.; Millman, S. R.
tbls.
pp. 517-547
Keywords: Nutricion; Calorias; Nutricion Infantil; Niños; Adultos; Regimen Alimentario; Mujeres; Alimentos